2018
DOI: 10.18321/ectj695
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Characteristics of Activated Carbons from Walnut Shells for Improved Supercapacitor Performance

Abstract: Activated carbons (ACs) have been prepared from chemical treatment of walnut shells (WS) precursor at various temperatures (400‒800 °C) by using phosphoric acid (H3PO4) as activating agent. Influence of activation temperature on the porosity development and capacitive properties of resulting carbons was investigated. Thermal post-treatment of carbons previously activated at moderate temperature, e.g. 400 °C allowed further structural and porosity modification. Then, these carbons were investigated by scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…From the obtained voltammograms illustrated in Fig. 4a, it was observed that all three types of electrode materials exhibit the nearly rectangular shape of cyclic voltammetry curves CVs, indicating a capacitive behavior that mainly arises from the charge and discharge of the EDL [20]. The highest capacitive current was observed for 2E cells based on RH-AC, while the lowest one for YP50F.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…From the obtained voltammograms illustrated in Fig. 4a, it was observed that all three types of electrode materials exhibit the nearly rectangular shape of cyclic voltammetry curves CVs, indicating a capacitive behavior that mainly arises from the charge and discharge of the EDL [20]. The highest capacitive current was observed for 2E cells based on RH-AC, while the lowest one for YP50F.…”
Section: Resultsmentioning
confidence: 89%
“…For CDI, the most promising materials for electrodes are those which have a high specific surface area, a large number of subnanometric pores, good electrical conductivity and low cost [13][14][15][16][17][18][19]. Due to these properties, nanoporous carbons have attracted the attention of researchers around the world [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время экономические причины и экологические проблемы привлекают значительное внимание исследователей к биомассе в качестве сырья для производства углеродных материалов. Так, в качестве прекурсора для получения активированного угля с большой площадью поверхности использовались древесина, листья, пивной осадок, рисовая шелуха и другие типы биомассы [4][5][6][7][8][9][10][11]. Активированные угли успешно получают из рисовой шелухи, карбонизированной в бескислородной атмосфере [12].…”
Section: Introductionunclassified
“…Another kind of capacitance is pseudo-capacitance; in this case, the charge is stored via fast reversible surface redox reactions [2,4,5]. High SSA nanomaterials like porous carbon, carbon nanotubes, and graphene are applied to reach high capacitance values for EDLC [6][7][8][9][10]. Various methods to produce porous carbon from different kinds of raw materials have been reported; recent research has focused on the utilization of renewable carbon precursors.…”
Section: Introductionmentioning
confidence: 99%